Analysis of The Characteristics of Porang Flour as A Coating Material After Treatment of NaCl Solution: Analysis of konjac flour after treatment of NaCl solution - Luh Suriati; I Gede Pasek Mangku; Anak Agung Sagung Manik_Chindrawati; Ni Luh Putu Sulis_Damayanti; Ngakan Putu Gede Satria_Kesumayasa; I Wayan Widiantara_Putra (SEAS (Sustainable Environment Agricultural Science), 2023)
The application of coatings from natural materials is currently needed to improve the appearance and maintain quality, so that it can support the green economy, namely increasing the welfare and social equality of the farming community. One of the basic ingredients in the manufacture of coatings from the polysaccharide group is konjac flour. The main problems faced in the development of konjac flour as a coating are that the color is still brown and itchy caused to the high content of calcium oxalate. Treatment with NaCl salt is one of the efforts to improve the quality of konjac flour as a coating material. Immersing konjac in NaCl salt solution repeatedly can reduce calcium oxalate. The reason of the observe became to decide the impact of the concentration and time of immersion of konjac slices into the salt solution of NaCl on the characteristics of the resulting konjac flour. This study used a two-factor randomized design, namely the concentration of NaCl salt solution (5, 10, and 15%) and the second factor was the immersion time (15, 30, and 45 minutes). Each treatment combination was repeated three times. The concentration and time of immersion into the salt solution of NaCl affected on color L*, browning index, water content, solubility, and acidity of konjac flour. The best treatment was soaking time of 30 minutes with NaCl concentration of 15%.